Psychological and Social Motivations in Microfinance Contracts: Theory and Evidence - Sanjit Dhami; Junaid Arshad; Ali al-Nowaihi (Center for Economic Studies and ifo Institute (CESifo), 2019)
Microfinance contracts have enormous economic and welfare significance. We study, theoretically and empirically, the problem of effort choice under individual liability (IL) and joint liability (JL) contracts when loan repayments are made either privately, or publicly in front of one's social group. Our theoretical model identifies guilt from letting down the expectations of partners in a JL contract, and shame from falling short of normatively inadequate effort, under public repayment of loans, as the main psychological drivers of effort choice. Evidence from our lab-in-the-field experiment in Pakistan reveals large treatment effects and confirms the central roles of guilt and shame. Under private repayment, a JL contract increases effort by almost 100% relative to an IL contract. Under public repayment, effort levels are comparable under IL and JL contracts, which is consistent with recent empirical results. This indicates that shame-aversion plays a more important role as compared to guilt-aversion. Under IL, repayment in public relative to private repayment increases effort by 60%, confirming our shame-aversion hypothesis. Under JL, a comparison of private and public repayment shows that shame trumps guilt in explaining effort choices of borrowers.
Keywords: C91; C92; D82; D91; G21; 330; microfinance; joint/individual liability; public/private repayment; belief-dependent motivations; guilt; shame; peer pressure; social capital; lab-in-the-field experiment